Was don José Duaso y Latre patriarch of the West Indies? - Torres-Remírez, José (Razón y fe, 2020)
History has many gaps that researchers are slowly trying to fill. However, there will always be dark spots. One of them is the ostentation of the position of Patriarch of the West Indies between the resignation of Antonio Allué Sesé and the appointment of Manuel Fraile García. The history of the West Indies Patriarchate and the life of Don José Duaso y Latre, the canon who is believed to have held the position of Patriarch for eight months, will be discussed.
Keywords: Catholic Church; 19th century; Carlist war; Goya; Fernando VII; absolutism